The Utilazation of Fisherman Catch for Nugget Product - Andi Rahmad Rahim; Ummul Firmani; Aminin Aminin; Sa’idah Luthfiyah; Sutrisno Adi Prayitno; Nur Maulida Safitri; Andrean Fajar Kusuma; Yusril Ihza Mahendra (Kontribusia : Research Dissemination for Community Development, 2020)
The fisheries sector is essential for the nourishment for marine life of coastal communities, use of fishery resources into livelihood of fishermen. In connection with that, this activity aims to increase the sale value of shrimp through counseling activities shrimp nuggets processing and product diversification. The method used is counseling and mentoring activities to produce diversified products which are followed by partner groups, especially women and housewives, as well as surrounding communities who have the desire to become entrepreneurs. The result is processed into products such as nuggets. The conclusion is that the shrimp commodity has a profitable business opportunity by increasing the selling price, so that it can increase the income of the community in the Kroman Village, Gresik District, Gresik Regency.